Comparison of Clinical Features between Primary Aldosteronism and Essential Hypertension in Chinese Patients: A Case-Control Study - Huang, Xiaoyu; Yu, Shuang; Xiao, Huangmeng; Pei, Ling; Chen, Yan; Chen, Wenzhan; Li, Yanbing; Xiao, Haipeng; Cao, Xiaopei (International journal of endocrinology, 2021)
Primary aldosteronism (PA) is one of the most common forms of secondary hypertension. Recent studies suggest that, compared with essential hypertension (EH), PA presents more severe disorders of glycolipid metabolism and organ damages. This case-control retrospective study aimed to ascertain clinical features and metabolic parameters between Chinese patients of PA and EH. 174 PA patients and 174 matched EH patients were recruited. Their clinical features, biochemistry parameters, the ventricular septal thickness, and left ventricular mass index (LVMI) were compared. HOMA-β% and HOMA-IR were calculated to evaluate glucose metabolism. The results showed that there was no significant difference regarding BMI, waist-to-hip ratio, and blood pressure between the two groups. The blood potassium level was significantly lower in PA patients than those in EH patients. The abnormal glucose tolerance and the incidence of diabetes in the PA group were not significantly different from those in EH group, but the insulin secretion levels at 0 min and 30 min were significantly weaker than those in the EH group, and the HOMA-β% was also lower in the PA group than those in the EH group. Left ventricular structural abnormalities in PA patients were more severe than those in EH patients. Subtype analysis indicated that patient with aldosterone-producing adenoma (APA) has more serious hypokalemia and lower levels of HOMA-β% and HOMA-IR comparing to those in the idiopathic adrenal hyperplasia (IHA) patient. These findings demonstrated that PA patients showed more impaired insulin secretion function and more severe left ventricular structural damage compared with EH patients.